Affective Dimensions of Language Testing: Insight from Participants in the Duolingo English Practice Test - Rika Lufiasari; Andi Rachmawati Syarif; Ririn Syahriani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the affective experiences of EFL learners when taking the Duolingo English Practice Test (DEPT). Using a qualitative descriptive approach, semi-structured interviews were conducted with five Indonesian EFL undergraduate students and analyzed through thematic analysis. The findings indicate recurring affective themes across participants namely test anxiety, motivation, self-confidence, attitudes toward the test, and perceived personal value while also showing individual variations in intensity. Initial anxiety, particularly in speaking and listening tasks, was commonly reported but tended to diminish as learners became familiar with the test format. The low-stakes nature of the DEPT encouraged positive attitudes, sustained motivation, and realistic self-assessment of English proficiency. Interpreted through Self-Determination Theory, these affective experiences were shaped by learners’ perceptions of autonomy and competence. The study highlights the potential of low-stakes digital practice tests as formative tools and offers implications for educators and test designers to integrate affective considerations into digital language assessment.